The influence of business associations on legislation: The case of Kenya. Issue 4 (20th November 2016) - Irwin, David; Githinji, Mary
Abstract : Interest groups seek to influence public policy. Business associations specifically seek to influence policy related to the environment in which their members operate, with the intention of making it easier for the members, and the wider private sector, to "do business." Scholars question whether interest groups are influential and, if so, the degree to which their activity influences public policy. Even if they do influence public policy at the margins, it is questionable how effective they are in influencing legislation. As a result, there is little exploration of the factors that may determine whether business membership organizations (BMOs) are likely to be successful. This paper explores the efforts of two BMOs in Kenya to influence legislation: In one case, the BMO persuaded the government to introduce legislation to regulate an activity that had previously not been subject to legislation; in the other, a BMO sought to persuade the government to amend its own proposals to replace existing legislation with new legislation. In both cases, we find evidence that the BMO was successful, though one BMO was significantly more successful than the other. We review the factors perceived by the BMOs to have led to their success. Neither was in a position to rely on economic or other power to strong‐arm the government. Both followed a predominantly insider strategy though with occasional media back‐up. Both were successful on the more "technical" issues. Key factors include the use of a champion, engaging across government, supplying information, and providing evidence and good argumentation.